Ungoverned Spaces and the Challenges of Terrorism in Africa - Rufus, Anthony Israel (Kashere Journal of Politics and International Relations, 2024)
Ungoverned Spaces and the Challenges of Terrorism in Africa explores the nexus between ungoverned territories and the proliferation of terrorism across the African continent. Ungoverned spaces, which refer to areas where state control is weak or non-existent, provide fertile ground for terrorist groups to thrive. These regions often suffer from poor governance, economic deprivation, and social marginalization, creating a vacuum in which extremist ideologies can easily take root. The article examines how terrorist groups, such as Boko Haram, Al-Shabaab, and ISIS affiliates, exploit these areas to establish operational bases, recruit fighters, and engage in illicit activities like arms smuggling and human trafficking. The article highlights the complex challenges African governments face in combating terrorism in ungoverned spaces, such as vast geographical areas, porous borders, and limited state capacity. Regional and international efforts to address these issues, including military interventions and capacity-building programs, are also discussed, emphasizing the need for a more holistic approach that includes addressing the underlying socio-economic and political drivers of extremism. Furthermore, the article argues that without significant improvements in governance, security, and development, these ungoverned spaces will continue to serve as sanctuaries for terrorist groups, posing a persistent threat to regional and global security. The conclusion calls for a coordinated, multi-faceted response that integrates local, national, and international efforts to restore state authority and promote sustainable peace and development in affected areas.